Dynamic tensile failure of rolled magnesium: Simulations and experiments quantifying the role of texture and second-phase particles. (March 2019) - Lloyd, J.T.; Matejunas, A.J.; Becker, R.; Walter, T.R.; Priddy, M.W.; Kimberley, J.
Abstract: The widespread use of magnesium alloys in applications that require high specific strength and stiffness has been hindered by its relatively low ductility. The hexagonal close-packed crystalline structure of magnesium alloys causes strong anisotropy in the mechanical response, which is reasonably well understood; however, the failure behavior is more complex. It is not clear whether the plastic anisotropy or the existence of second phase particles control failure, and to date, more attention has been given to the former than the latter. In this work, a series of high-rate tension experiments were performed on thin foil specimens of hot rolled magnesium alloy AZ31B using a miniaturized tensile Kolsky bar along an array of angles in the normal-rolling plane at strain rates of nominally 10 4 s − 1 . These experiments are compared with a set of finite element computations employing crystal plasticity and direct numerical simulation of void-nucleating second phase particles measured using micro-CT. Simulations are used to quantify the relative role that plastic anisotropy and second phase particle morphology play in dictating the failure response of rolled magnesium. Results indicate that plastic anisotropy dictates the way that voids grow and coalesce, and that in some cases, the pronounced plastic anisotropy of magnesium increases, rather than decreases, the maximum strain to failure. In all cases, the large second phase particles in rolled magnesium AZ31B greatly reduce the maximum failure strain as compared with an equivalent volume fraction of randomly distributed spherical particles. Additionally, it is shown that simulations lacking a proper description of orientation-dependent plastic anisotropy and particle morphology do not correlate well with measured failure behavior. Graphical abstract: Image 1 Highlights: Dynamic tensile experiments are conducted to relate the failure strain as a function of processing direction in magnesium. Simulations of dynamic failure were performed based on voids nucleated from experimentally measured second phase particles. Simulations that included realistic second phase particles and crystal plasticity compared favorably with experiments. Simulations that approximated particles as spheres or the material as isotropic failed to predict experimental measurements. Orientation-induced anisotropy in magnesium does not always reduce ductility.